Role of Chemically Modified Tetracyclines in the Management of Periodontal Diseases: A Review - Ghangurde, Archit A.; Ganji, Kiran Kumar; Bhongade, Manohar L.; Sehdev, Bhumika (Drug Research, 2017)
Researchers have found that Chemically Modified Tetracyclines (CMTs) act through multiple mechanisms, affecting several parameters of osteoclast function and consequently inhibit bone resorption by altering intracellular calcium concentration and interacting with the putative calcium receptor; decreasing ruffled border area; diminishing acid production; diminishing the secretion of lysosomal cysteine proteinases (cathepsins); inducing cell retraction by affecting podosomes; inhibiting osteoclast gelatinase activity; selectively inhibiting osteoclast ontogeny or development; and inducing apoptosis or programmed cell death of osteoclasts. Thus TCs/CMTs, as anti-resorptive drugs, may act similarly to bisphosphonates and primarily affect osteoclast function. Researchers have evaluated the influence of various chemically modified tetracyclines from CMT-1 to CMT-10 on collagenases and gelatinases through in vitro or animal studies and concluded that all the CMTs except CMT-5 inhibited periodontal breakdown through MMP inhibition in the following order of efficacy: CMT-8>CMT-1>CMT-3>CMT-4>CMT-7. Thus the non-antimicrobial actions of the chemically modified analogues of tetracyclines have shown remarkably better mechanisms to those of agents with established anti-inflammatory/antioxidant potential. These findings clarify the multi-faceted actions of tetracyclines which are unique amongst antimicrobials, with therapeutic applications in periodontal and metabolic diseases. Hence, the present review describes the role of chemically modified tetracyclines in the management of periodontal diseases.
Keywords: chemically modified tetracyclines; periodontitis; anticollagenolytic